THE EFFECT OF ADDING VITAMIN C TO COMMERCIAL FEED ON THE GROWTH AND SURVIVAL OF CANTANG GROUPER FISH - Dewi, Nyoman Trisna Wahyu Maria; Sitepu, Gressty Sari Br; Antara, Kadek Lila (Jurusan Perikanan dan Kelautan, 2025)
This study was conducted to scientifically evaluate the effect of vitamin C supplementation in commercial feed on the growth performance and survival rate of cantang grouper (Epinephelus fuscoguttatus × E. lanceolatus), a high-value aquaculture commodity in Indonesia. The experimental design employed was a Completely Randomized Design (CRD) with three treatments: commercial feed without vitamin C (control), feed supplemented with 20,000 ppm of vitamin C, and feed supplemented with 40,000 ppm of vitamin C, each with three replicates. The key parameters observed included weight gain, specific growth rate (SGR), and survival rate (SR) of the fish during a 30-day rearing period. The results revealed that the addition of vitamin C to the commercial feed had a statistically significant effect on both weight gain and SGR (p < 0.05), where the 40,000 ppm treatment produced the highest mean weight gain (7.12 grams) and SGR value (0.0765%). Although survival rate did not differ significantly among treatments (p > 0.05), the group receiving 40,000 ppm of vitamin C still achieved the highest survival rate of 100%. Water quality parameters, including temperature, pH, salinity, dissolved oxygen, and ammonia, remained within optimal ranges throughout the experiment in accordance with marine aquaculture standards. Based on these findings, it can be concluded that vitamin C supplementation, particularly at a concentration of 40,000 ppm, is highly effective in promoting growth performance and maintaining high survival rates of cantang grouper under controlled aquaculture conditions.